Dinamika Kebijakan Penyetaraan Sistem Pendidikan Pesantren Dalam Konteks Pendidikan Nasional - Muhammad Ismail; Saifudin Asrori (Jurnal Inovasi dan Kreativitas (JIKa), 2023)
Problems: Government policy on equalizing the Islamic boarding school education system with equivalent educational entities or muaddalah raises concerns among the pesantren community that the essence and distinctive nature of religious education, which has been the identity of pesantren for years, may undergo changes. Purpose: The purpose of this article is to depict the ability of the Islamic boarding school education system to adapt to the evolution of government policies, transitioning from marginalization and discrimination against pesantren to recognition as religious educational institutions. This transformation ultimately leads to achieving the level of equality (muaddalah) as formal educational entities in Indonesia Methodology: The research is conducted using a quantitative approach with a case study design on the adaptation mechanisms of the education system at Pondok Gontor, East Java, towards muaddalah policies. Results/Findings: The results of this research indicate that the institutional approach illustrates that educational institutions are entities with formal and rational management structures but have loose connections in educational activities. Policy alignment is carried out innovatively and dynamically, where the education system of Kulliyatul Muallimin al-Islamiyah (KMI) officially adopts accreditation mechanisms, management evaluation, teacher qualifications, curriculum standards, and educational infrastructure in accordance with government policies. Nevertheless, the commitment as an educational institution, a place where students study religious knowledge (tafaqquh fi ad-din), shape the character of students, and enhance skills to contribute to societal progress, remains steadfast and unchanged. Paper Type: Implementation policy research